Billboard for The Grapes of Wrath - Dorothea Lange:::Creator::::::::::::
Billboard for The Grapes of Wrath movie. Anecdotal note to Steinbeck from photographer on back. Original in safe Lange's photographs influenced the development of documentary photography and humanized the consequences of the Great Depression.